COMMUNICATION VALUES OF CORPORATE MANAGEMENT IN THE CONDITIONS OF DIGITAL CULTURE DEVELOPMENT - Alla; tymoshenko, dmytro (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Abstract. The article substantiates the expediency of communication values application in corporate management. Particular attention is paid to the retrospective of the digital transformation strategy within the context of technocratic culture phenomena. Attention is paid to communication values, providing effective corporate management policy and taking into account the requirements, challenges and trends of modern development, which allows both, to attract and maintain relevant communications with all stakeholders. It is proved that the attention to this topic is justified by the trends of modern development: globalization requirements, innovative development, as well as the digital transformation of all organizations. The complexity of the category of ‘culture’ is shown; the peculiarities of corporate management subjects within the relationship between it and global challenges — excessive psychological, intellectual, social, technological overload are taken into account. It is shown that digital strategy is, in fact, a strategic development plan of a modern corporation, which determines the priorities of its activities and the best ways to achieve them. The influence of philosophical phenomena upon the communication process is analyzed. The characteristic of communication formations preconditions (and it values) both within of the fourth industrial revolution implementation, and the COVID-19 virus distribution is given. Particular attention is paid to the main trends in the area of employment in the digital economy. The trends that corporations face when changing the context of communication values are indicated — in general, we can identify the following areas of their formation and development. Emphasis is placed on the positive experience of domestic enterprises in ideology of turquoise organizations application in the corporate culture area, which are characterized by a high level of self-organization and self-management.